Adults With Persistent ADHD: Gender and Psychiatric Comorbidities—A Population-Based Longitudinal Study. Issue 6 (April 2018) - Yoshimasu, Kouichi; Barbaresi, William J.; Colligan, Robert C.; Voigt, Robert G.; Killian, Jill M.; Weaver, Amy L.; Katusic, Slavica K.
Objective: The aim of the study was to evaluate associations between ADHD and comorbid psychiatric disorders among adults from a population-based birth cohort.Method: Participants were recruited from all children born between 1976 and 1982 remaining in Rochester, Minnesota, after age 5. Participants with childhood ADHD ( n = 232; M age = 27.0 years; 72% men) and non-ADHD controls ( n = 335; M age = 28.6 years; 63% men) completed a structured interview (M.I.N.I. International Neuropsychiatric Interview) assessing current ADHD status and comorbid psychiatric disorders.Results: Among 232 with childhood ADHD, 68 (49 men, 19 women) had persistent adult ADHD. Compared with non-ADHD controls and non-persistent ADHD participants, adults with persistent ADHD were significantly more likely to have any or each of 12 psychiatric comorbidities. The associations retained significant or marginally significant when stratified by gender. Externalizing psychiatric disorders were more common in men (74%) and internalizing disorders in women (58%).Conclusion: Persistent ADHD is associated with an increased risk of comorbid psychiatric disorders in adult men and women.